2008
DOI: 10.1016/j.ajhg.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent CNVs Disrupt Three Candidate Genes in Schizophrenia Patients

Abstract: Schizophrenia is a severe psychiatric disease with complex etiology, affecting approximately 1% of the general population. Most genetics studies so far have focused on disease association with common genetic variation, such as single-nucleotide polymorphisms (SNPs), but it has recently become apparent that large-scale genomic copy-number variants (CNVs) are involved in disease development as well. To assess the role of rare CNVs in schizophrenia, we screened 54 patients with deficit schizophrenia using Affymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
191
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(203 citation statements)
references
References 45 publications
(61 reference statements)
8
191
1
3
Order By: Relevance
“…38 CTNND2 has been associated with intellectual disability in cri-du-chat syndrome 36 (OMIM 604275), autism when deleted, 38,39 and schizophrenia when duplicated. 37 Previous studies have reported both dosage variation and disruptive effects resulting from CNVs involving CTNND2. 37,40 This gene has a predicted HI of 26.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 CTNND2 has been associated with intellectual disability in cri-du-chat syndrome 36 (OMIM 604275), autism when deleted, 38,39 and schizophrenia when duplicated. 37 Previous studies have reported both dosage variation and disruptive effects resulting from CNVs involving CTNND2. 37,40 This gene has a predicted HI of 26.1%.…”
Section: Discussionmentioning
confidence: 99%
“…37 Previous studies have reported both dosage variation and disruptive effects resulting from CNVs involving CTNND2. 37,40 This gene has a predicted HI of 26.1%. (v) A 219-bp duplication in case P025 involving exon 1 of MCPH1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MYT1L gene encodes for a C2HC-type zinc finger transcription factor highly expressed in developing neuronal cells. 17 When duplicated this gene has been associated with schizophrenia 18,19 and major depressive disorder. 20 Heterozygous loss of function of the MYT1L gene deleted in all our patients could be responsible for the behavioural difficulties and psychomotor retardation described in patients with 2pter deletion as proposed by Stevens et al 7 All patients (P1-5) have mild to severe ID.…”
Section: Id/behavioural Troublesmentioning
confidence: 99%
“…36 Another group of researchers identified 90 CNVs in 54 patients, of which 13 were rare CNVs disrupting genes associated with SZ such as MYT1L, CTNND2 and ASTN2. 37 To confirm the association of these rare CNVs a large cohort of samples is needed.…”
Section: Cnv and Neurological Disordersmentioning
confidence: 99%